The Relationship between Parenting Patterns and Interest in Learning in Class V Students of SDN 006 Petani Pelalawan District - Nopriani, Shela; Ain, Siti Quratul (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The purpose of conducting this research is to find out whether there is an influence between the parenting style carried out by parents on students’ interest in learning. This research uses a correlation-based quantitative approach. This research was carried out in June – July 2024. The population of this research was all class V students at SDN 006 Tanjung Bunut, Pelalawan Regency. This research was attended by 44 class V students of SDN 006 Tantani, Bunut District, Pelalawan Regency as respondents. Data for this research was collected through the use of documentation and questionnaires. The results of the research show that the parenting style of class V students at SDN 006 Tantani, Pelalawan Regency has an influence on students’ enthusiasm for learning. The influence of parental parenting on students’ enthusiasm for learning is classified as "medium" or rather high in class V of SDN 006 Tantani, Pelalawan Regency with a value of 0.783